Stenotrophomonas maltophilia causing blood stream infection in neonates and infants: a cause for concern. (July 2018) - Sah, Rinku; Siwakoti, Shraddha; Baral, Ratna; Rajbhandari, Rupa S; Khanal, Basuda
Stenotrophomonas maltophilia ( S. maltophilia ) is an important Gram-negative, non-fermentative, multidrug resistant (MDR) nosocomial organism. We evaluated the isolation of S. maltophilia from the seven blood culture specimens received from the Paediatric Emergency Department (PED) of BP Koirala Institute of Health Sciences (BPKIHS) over the duration of two weeks. The suspicion of a possible outbreak was raised and the hospital infection control team investigated the source and found the hand of one healthcare provider harbouring a similar organism. All six steps of hand hygiene were subsequently strictly enforced after which the same bacteria were no longer isolated. Infection control measures should be rigorously adopted for the control of such nosocomial bacteria.